#### Answer

-4

#### Work Step by Step

We know that $\sqrt[3] -64=-4$, because $(-4)^{3}=-4\times-4\times-4=-64$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

-4

We know that $\sqrt[3] -64=-4$, because $(-4)^{3}=-4\times-4\times-4=-64$.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.